Imobilização de Saccharomyces cerevisiae em bagaço de cana-de-açúcar e alginato, para a produção de etanol - Guardiano, Jefferson (2018)
Ethanol is considered to be a biofuel obtained from sugar cane (Saccharum spp.), produced by means of the alcoholic fermentation process, with the use of yeasts, which make the bioconversion of the available sugars in their broth to the ethanol. This process has as its main by-products sugarcane bagasse, vinasse and glycerol, which can be recycled in the process or to obtain the second generation ethanol, obtained through the hydrolysis of sugarcane bagasse or the bioconversion of vinasse. The biggest leaders when it comes to ethanol productivity are Brazil, using sugarcane, and the United States, making use of corn. Given the high cost of oil barrels and the volume of by-products generated, they are interested in investing in renewable energy sources and / or new technologies by applying their by-products. Based on this level, ethanol ends up being the most important biofuel and its bioprocess is commonly studied, searching for new methodologies, yeast cultures, ways to improve its yields and new techniques to reuse the generated waste. Based on this idea, the present study aimed to immobilize Saccharomyces cerevisiae yeast in sugarcane bagasse using two immobilization techniques (surface adsorption and encapsulation), which was then applied in an alcoholic fermentation process. For this, the support medium was formulated, immobilizing the yeast in sugarcane bagasse and imprisoning with sodium alginate. This immobilized was applied in tests of alcoholic fermentation, considering two different temperatures of incubation (28 °C and 34 °C) comparing the free yeast with the immobilized yeast. Subsequently, these samples were distilled for analysis of their alcohol content and secondary metabolites (acetaldehyde, ethyl acetate, 1-propanol, isobutanol, isoamyl alcohol and isoamyl acetate) by gas chromatography (GC). As a result, yeast immobilization was obtained in the support suitably developed for the production of ethanol. In relation to the analytical results of the fermentations, it was possible to identify significant differences in acetaldehyde production for free yeasts at 28 °C (21,65 mg.L-1 ), ethyl acetate for immobilized at 28 °C (26,37 mg.L-1 ), 1-propanol for immobilized at 28 °C (20,46 mg.L-1 ) and isobutanol for those immobilized at 34 °C (37,64 mg.L-1 ). There was no significant difference for the production of ethanol, isoamyl acetate and isoamyl alcohol.